Biomimetic Nanomaterials Triggered Ferroptosis for Cancer Theranostics - Zhang, Xinyu; Ma, Yanling; Wan, Jipeng; Yuan, Jia; Wang, Diqing; Wang, Weiyi; Sun, Xiao; Meng, Qingwei (Frontiers in Chemistry, 2021)
Ferroptosis, as a recently discovered non-apoptotic programmed cell death with an iron-dependent form, has attracted great attention in the field of cancer nanomedicine. However, many ferroptosis-related nano-inducers encountered unexpected limitations such as immune exposure, low circulation time, and ineffective tumor targeting. Biomimetic nanomaterials possess some unique physicochemical properties which can achieve immune escape and effective tumor targeting. Especially, certain components of biomimetic nanomaterials can further enhance ferroptosis. Therefore, this review will provide a comprehensive overview on recent developments of biomimetic nanomaterials in ferroptosis-related cancer nanomedicine. First, the definition and character of ferroptosis and its current applications associated with chemotherapy, radiotherapy, and immunotherapy for enhancing cancer theranostics were briefly discussed. Subsequently, the advantages and limitations of some representative biomimetic nanomedicines, including biomembranes, proteins, amino acids, polyunsaturated fatty acids, and biomineralization-based ferroptosis nano-inducers, were further spotlighted. This review would therefore help the spectrum of advanced and novice researchers who are interested in this area to quickly zoom in the essential information and glean some provoking ideas to advance this subfield in cancer nanomedicine.